An investigation on the Vitamin A1, C and E contents of freswater mussel, Unio elongatulus eucirrus Bourguignat 1860 - Özdemir, Yaşar; Koprucu, Kenan; Şeker, Engin (My University, 2000)
Vitamin A2, C and E contents in the muscle of freshwater mussel, U. elongatulus eucirrus were investigated in the present study. The results showed that freshwater mussel constitutes 2.4+0.1 $\\mu$.g $g^{-1}$ vitamin A2, 25.9±1.7$\\mu$.g $g^{-1}$ vitamin C and 26.6±1.1 $\\mu$.g $g^{-1}$ vitamin E. Correlations between muscle weight of the freshwater mussel A7, C and E vitamin contents were determinated significant (r = 0.53, r = 0.53 and r = 0.81 respectively). It was obtained that the parallel of muscle weight increase of the freshwater mussels, which were increase A2, C and E vitamin contents of muscle, too. Under the light of this study, it is concluded that freshwater mussel possesses higher vitamin C and E contents than many commercial fish species.
Keywords: Unio elongatulus eucirrus; vitamin E; mussels; ascorbic acid; fresh water; muscles; dehydroretinol; vitamin content